Web mode as part of mixed-mode surveys of the general population - Berzelak, Jernej (Metodološki zvezki, 2015)
Lower data collection costs make web surveys a promising alternative to conventional face-to-face and telephone surveys. A transition to the new mode has already been widely initiated in commercial research, but web surveys remains limited in academic and official research projects that typically require probability samples and high response rates. Various design approaches for coping with the problems of sampling frames, incomplete Internet use, and nonresponse in web surveys have been proposed. Mixed-mode designs and incentives are two common strategies to reach Internet non-users and increase the response rates in web surveys. However, such survey designs can substantially increase the costs, the complexity of administration and the possibility of uncontrolled measurement effects. This paper presents and demonstrates an approach to the evaluation of various survey designs with simultaneous consideration of the errors and costs. It focuses on the designs involving the web mode and discusses their potential to replace traditional modes for probability surveys of the general population. The main idea of this approach is that part of the cost savings enabled by the web mode can be allocated to incentives and complementary survey modes to compensate for the Internet non-coverage and the higher nonresponse. The described approach is demonstrated in an experimental case study that compares the performance of mixed-mode designs with the web mode and prepaid cash incentive with that of an official survey conducted using the face-to-face and telephone modes. The results show that the mixed-mode designs with the web mode and incentives can greatly increase the response rate, which even surpasses that of the conventional survey modes, but still offer substantial cost savings. However, the results also show that higher response rate does not necessary translate to higher data quality, especially when the main aim is to obtain estimates that are highly comparable with those of the reference survey.
Keywords: Statistics; Statistika; Statistical data; Statistični podatki; spletne ankete; stroški; napake